Dentists and hepatitis B vaccination – An "In Vivo" National Study - YARED , Ghassan; AL-KHATIB , Aynaa; EL MANHAL, Wassim; YARED , Nathalie; YOUNES, Ronald (International Arab Journal of Dentistry (IAJD), 2023)
Introduction: Hepatitis B continues to be a serious occupational concern for dental healthcare practi tioners, with the possibility of transmission occurring during patient care practices. The incidence of hepatitis B amongst dentists, the factors raising their occupational risk, and the efficiency of vaccina tion programs in reducing this risk are all examined in this paper’s methodical evaluation of the body of prior research. This study addresses the important confluence of hepatitis B infection, occupational exposure, and vaccination status amongst dentists. In addition, it provides methods for improving the protection of dental professionals against hepatitis B infection by summarizing major findings and high lighting gaps in current knowledge, assuring the safety of both healthcare workers and their patients. The main objective of the study is to assess the relationship between Hepatitis B vaccination status and immunization level as measured by anti-HBs titer among a population of 192 dentists in Lebanon. Materials & Methods: 192 dentists, underwent the anti-HBs titer blood test. This test, which is Elecsys Anti-HBs, was used for the quantitative assessment of antibodies against the HBsAg. Results: The chi-square test was used to assess the association between being vaccinated against Hepatitis B and being immunized against the disease. A significant association was found between vaccination and immunity status. Among those vaccinated against Hepatitis B, 86.7% were found to be immune based on the blood test results versus 36.0% of those not vaccinated (p<0.001). Conclusion: the current study’s It highlights how crucial it is to keep up efforts to increase vaccination rates and promote immunization in order to improve population health and well-being in general. A dentist can play a part in hepatitis prevention by treating each and every patient as a possible hepatitis carrier.